2017
DOI: 10.4049/jimmunol.1600954
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Phosphatidylinositol 3-Kinase δ Signaling Leads to Diminished Numbers of Regulatory T Cells and Increased Neutrophil Activity Resulting in Mortality Due to Endotoxic Shock

Abstract: Despite decades of clinical and biomedical research, the pathogenesis of sepsis and its spectrum of diseases (severe sepsis and septic shock), which are leading causes of death in intensive care units, are still poorly understood. In this article, we show that signaling via the p110δ isoform of PI3K is critical for survival in experimental sepsis. Mice with an inactive knock-in mutation in the p110δ gene (p110δ) succumbed acutely to nonlethal dose LPS challenge. The susceptibility of p110δ mice to LPS was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…For example, we previously showed that depletion of Tregs leads to exaggerated CD4 + T cell response in bacteria and LPS-induced acute inflammation models (61). In another study, we demonstrated that reduced Treg numbers also leads to enhanced neutrophil activity in LPS-induced inflammation (150). Hence, it follows that reduced Treg numbers simultaneously affects CD4 + T cells and neutrophils.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, we previously showed that depletion of Tregs leads to exaggerated CD4 + T cell response in bacteria and LPS-induced acute inflammation models (61). In another study, we demonstrated that reduced Treg numbers also leads to enhanced neutrophil activity in LPS-induced inflammation (150). Hence, it follows that reduced Treg numbers simultaneously affects CD4 + T cells and neutrophils.…”
Section: Discussionmentioning
confidence: 96%
“…Richards et al showed that Tregs limit inflammation in the skin by inhibiting neutrophil accumulation and survival (149). We recently showed that reduced Treg numbers in mice leads to exaggerated neutrophil activity resulting in mortality in endotoxic shock (150). We also found that Tregs regulate survival and activity of human and murine neutrophils and co-culture of Tregs and neutrophils increases neutrophil apoptosis (150).…”
Section: Tregs and Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defective Treg function were demonstrated in all these diseases, and Treg therapy ameliorated them [ 67 ]. Reduced Treg numbers in mice leads to exaggerated neutrophil activity resulting in mortality in endotoxic shock [ 68 ]. Tregs regulate survival and activity of human and murine neutrophils, and co-cultures of Tregs and neutrophils increases neutrophil apoptosis [ 68 ].…”
Section: Trained Immunity and Neutrophil Hyper-responsivenessmentioning
confidence: 99%
“…The importance of the PI3K pathway in human immune disorders is further emphasized by the presence of activating mutations in p110δ in a number of primary immune deficiency patients, who suffer particularly from recurring respiratory tract infections (105). In contrast, deficiency in PI3Kδ signaling decreases Treg number and increases neutrophil numbers, which can cause an increase in endotoxic shock-related mortality (106).…”
Section: Phosphoinositidesmentioning
confidence: 99%